TANTANG AN DAN PELUANG PEMBENTUKAN BANK BUMN SYARIAH DALAM MENYAMBUT ASEAN ECONOMIC COMMUNITY 2015 - Anna Marina; Sentot Imam Wahjono; Ezif Muhammad Fahmi (UMSurabaya Publishing, 2014)
The aim of this study is to conduct a scientific study on the challenges and opportunities of the establishment of Islamic banks in Indonesia, which is majority owned by the State Ownership Corporation (BUMN). During 21 years of operation of Islamic banking in Indonesia accounted for only 5% of the national banking system, while it welcomed the ASEAN Community in 2015 will open opportunities entrants from foreign countries in the Indonesian banking market, especially from Malaysia, which already has a strong Islamic banks and big. Therefore in this paper presented are the challenges and opportunities in establishing Islamic bank with PT Bank BRI Tbk convert into sharia and was soon followed by the acquisition of three other state-owned Islamic bank so that the new Islamic bank(Bank Syariah Indonesia) has the potentialo be the largest Islamic bank in the world